Efficacy of Mycophenolate Mofetil and Oral Cyclophosphamide on Skin Thickness: Post Hoc Analyses From Two Randomized Placebo‐Controlled Trials. Issue 3 (9th February 2018) - Namas, Rajaie; Tashkin, Donald P.; Furst, Daniel E.; Wilhalme, Holly; Tseng, Chi‐Hong; Roth, Michael D.; Kafaja, Suzanne; Volkmann, Elizabeth; Clements, Philip J.; Khanna, Dinesh; ,
Abstract : Objective: To assess the efficacy of mycophenolate mofetil (MMF) and cyclophosphamide (CYC) on modified Rodnan skin score (MRSS) in participants enrolled in the Scleroderma Lung Study (SLS) I and II. Methods: SLS I participants received daily oral CYC or matching placebo for 1 year, whereas SLS II participants received daily MMF for 2 years or daily oral CYC for 1 year followed by placebo for second year. We assessed the impact of MMF and CYC on the MRSS in SLS II over a 24‐month period. We also compared the change in MRSS in patients with diffuse cutaneous systemic sclerosis (dcSSc) assigned to CYC and MMF in SLS II and SLS I versus placebo in SLS I over a 24‐month period using a linear mixed model. Results: In SLS II, the baseline mean ± SD MRSS was 14.0 ± 10.6 units for CYC and 15.3 ± 10.4 units for MMF; 58.5% were classified as dcSSc. CYC and MMF were associated with statistically significant improvements in MRSS from baseline over the period of 24 months in dcSSc ( P < 0.05 at each time point), but there were no differences between the 2 groups. In the dcSSc subgroup, the change in MRSS from baseline to all 6‐month visits was similar in SLS II groups (MMF, CYC, pooled cohort [MMF + CYC]) and in the SLS I CYC group and showed statistically significant improvements compared to SLS I placebo at 12, 18, and 24 months ( P < 0.05). Conclusion: In SLS II, MMF and CYC treatment resulted in improvements in MRSS in patients with dcSSc over 24 months. In addition, MMF and CYC treatment resulted in statistically significant improvements in MRSS in patients with dcSSc when compared with the SLS I placebo group.